1985
DOI: 10.1080/01904168509363360
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum effects on uptake and translocation of nitrogen in sorghum (Sorghum bicolor, L. Moench)

Abstract: The effects of aluminum on the uptake and translocation of N in two hybrid cultivars of sorghum with differential tolerance to aluminum were studied.Aluminum decreased the amount of N accumulated and the % of N in the aerial parts of the plants. In the roots the amount of N accumulated also decreased but the % of N increased, in both cultivars. Besides an effect on dry matter yield, Al probably reduces the uptake of N and its translocation to the aerial parts of the plant. Apparently, this impairment on N tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 12 publications
1
9
0
3
Order By: Relevance
“…However, A1 reduces NO 3 uptake in the NB9040 cultivar much stronger than the uptake of the other anions. Results of this experiment agree with findings of Gomes et al (1985), who found an Al-induced reduction of the uptake of nitrogen in sorghum plants. From our findings it becomes clear that in a NH4NO3 system this reduction of N uptake must be completely attributed to a reduced NO3 uptake.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, A1 reduces NO 3 uptake in the NB9040 cultivar much stronger than the uptake of the other anions. Results of this experiment agree with findings of Gomes et al (1985), who found an Al-induced reduction of the uptake of nitrogen in sorghum plants. From our findings it becomes clear that in a NH4NO3 system this reduction of N uptake must be completely attributed to a reduced NO3 uptake.…”
Section: Discussionsupporting
confidence: 94%
“…Gomes et al (1985) found that A1 had pronounced effects on the acquisition and assimilation of N in sorghum. In an Al-susceptible wheat cultivar Foy and Fleming (1982) found negative effects of A1 on the nitrate reductase activity (NRA), the first enzyme involved in the NO3 assimilation in plants.…”
Section: Introductionmentioning
confidence: 98%
“…O teor de N na matéria seca da parte aérea e das raízes da Moringa diminuiu com o incremento na concentração de Al na solução nutritiva (Figura 1), o que corrobora com os resultados de Gomes et al (1985) e Cambraia et al (1990). O Al, quando é encontrado em teores tóxicos, interfere na aquisição e no metabolismo nitrogenado, havendo diminuição na absorção, translocação e redução do nitrato em raízes (Gomes et al, 1985;Cambraia et al, 1989).…”
Section: Resultsunclassified
“…O Al, quando é encontrado em teores tóxicos, interfere na aquisição e no metabolismo nitrogenado, havendo diminuição na absorção, translocação e redução do nitrato em raízes (Gomes et al, 1985;Cambraia et al, 1989). No Angico, ocorreu incremento do teor de N na matéria seca das raízes com o incremento na concentração de Al na solução nutritiva, e na parte aérea não houve efeito do Al no teor de N.…”
Section: Resultsunclassified
“…Também é possível que ele estimule a absorção de amônio mediante efeito modulador positivo sobre a sintetase da L-glutamina das células radiculares. Diferentemente disso, GOMES et al (1985) e CAMBRAIA et al (1989 Tabela 3 -Teor de nitrogênio no colmo principal, nos afilhos A1 e A2 de trigo, em três níveis de correção do solo (telado) ou três concentrações de alumínio na solução (câmara de crescimento), em quatro épocas de aplicação de nitrogênio. * Médias seguidas pela mesma letra maiúscula na horizontal e minúscula na vertical não diferem estatisticamente pelo teste de Duncan, ao nível de significância de 5%.…”
Section: -------------------------------Espigas Por áRea Em Telado (Nunclassified